Pengaruh Jenis Bahan Campuran dalam Re-Kompos Residu Teh Kompos terhadap Pertumbuhan Dan Hasil Tanaman Bayam (Amaranthus tricolor, L.) - Eduardus Y Neonbeni; Maria Kornelia Oki (Fakultas Pertanian, Universitas Timor, 2019)
Compost residue is organic waste that can be reused as organic fertilizer through re-composting using a mixture of organic matter. A pot experiment was carried out using a mixture of siam weed forage and biochar for composting the compost residue in utilization as a medium for growing spinach (Amaranthus tricolor L.). This research discusses the spinach growth and yield affected by compost that has been recompost. This research conducted in March-April 2019 at the faculty of agriculture demo-plot, Universitas Timor. The design used was a two-factor of factorial completely randomized design with 3 replications. The first factor of treatment was the percentage of the composition of biochar mixture consisting of control, compost tea residue+ 2.5% of biochar, compost tea residue+5 % of biochar, and tea compost residue+10% of biochar. The second factor was the percentage of the siam weed forage namely control, compost tea residue+ 2.5% of siam weed forage, compost tea residue+5 % of siam weed forage, and tea compost residue+10% ofsiam weed forage. The results of Anova variance showed that there was an interaction of adding 10% of biochar re-compost and 10% of siam weed forage re-compost effect on plant height 28 DAS (15.42 cm), stem diameter 28 DAS (0.54), leaf number 21 (6, 50 strands) and 28 DAS (9.17 strands), plant fresh weight (19.22 g), fresh trubus weight (16.81 g) and root length of spinach plant (13,17 cm). The combination of adding10% of biochar re-compost and 10% of siam weed forage re-compost is the best treatment, significantly different withothers treatment.